Participatory Research For Natural Resource Management: Continuing to Learn Together - CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation; Natural Resources Institute (CGIAR System Organization, 1999)
Case studies on participatory research for natural resource management